Efficiency of shoot regeneration and micropropagation of purple passion fruit (Passiflora edulis Sims.) via internodal longitudinal thin cell layer culture - Hieu, Tran; Tung, Hoang Thanh; Nguyen, Cao Dang; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2020)
The thin cell layer culture technique (TCL) has been used for the effective tissue culture of several dozen plants with commercial importance such as field crops (rice, cereals), horticultural commodities (fruits, vegetables, ornamental plants), medicinal plants and herbs (Panax vietnamensis Ha et Grushv.), and even forestry trees (Pinus sp.), and woody fruit plants (Citrus spp., apple). In the present, TCL was used to evaluate the efficiency of shoot regeneration and propagation for purple passion fruit (Passiflora edulis Sims.). The internodes were cut longitudinally (lTCL) and was used as an initial material. The results showed that the shoot regeneration rate and number of shoots from internode-lTCL depended on position of internodes (1, 2, 3, 4 and 5) and the plant growth regulator (BA and NAA). After 8 weeks of culture, internode-lTCL derived from 3rd internode of P. edulis cultured on MS medium supplemented with 1.5 mg/L BA in combination with 1.0 mg/LNAA gave the highest shoot regeneration rate (83.33%), and number of shoots (3.00 shoots/explant). These shoots were cultured on modified MS (MSM) medium supplemented with 1.0 mg/L BA showed higher efficiency of shoot multiplication (3.56 shoots/explant and 6.67 cm height) than the other BA treatments. In addition, the highest rooting rate was 76.67% when cultured on MSM medium containing 2.0 mg/L IBA. The survival rate of plantlets was 83.33% when transferred into greenhouse condition after 10 weeks. The results of this study were the initial success in establishing an effective in vitro regeneration and propagation of Passiflora edulis Sims. through internode-lTCL.